2017
DOI: 10.3892/mmr.2017.7716
|View full text |Cite
|
Sign up to set email alerts
|

Kangfuxin promotes apoptosis of gastric cancer cells through activating ER-stress and autophagy

Abstract: Gastric cancer is a leading cause of cancer‑associated mortality worldwide. In studies on the mechanisms of antigastric cancer drugs, autophagy and endoplasmic reticulum (ER) stress have been demonstrated to serve an active role in gastric cancer. The organic extract of Periplaneta americana (also termed American Cockroach), which is named Kangfuxin (KFX) in China, has been used clinically as a traditional Chinese medicine against disorders, including stomach bleeding, gastric ulcers, tuberculosis, burns and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Although our group has previously confirmed the gastroprotective effects of KFX in ethanol-induced gastric ulcer and gastric cancer (Chen et al. 2017; Shen et al. 2017), little is known about its potential therapeutic effects on stress-induced gastric ulcer.…”
Section: Discussionmentioning
confidence: 87%
“…Although our group has previously confirmed the gastroprotective effects of KFX in ethanol-induced gastric ulcer and gastric cancer (Chen et al. 2017; Shen et al. 2017), little is known about its potential therapeutic effects on stress-induced gastric ulcer.…”
Section: Discussionmentioning
confidence: 87%
“…31 The study of Ogata M et al indicated that there was a close relation between targeting the autophagy mechanisms and ER stress pathway. 32 ER stress and autophagy seems to be critical for oncogenesis and cell homeostasis. Melatonin, a naturally occurring compound with clear potent inhibitory effects on cancer cells is one of the main candidates, which can be recruited herein.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigation into more effective therapeutic interventions for gastric cancer is important. Over the last 50 years, emerging evidence has suggested that a number of natural extracts from plants and animals exhibit beneficial effects in the prevention of cancer ( 16 , 38 , 39 ). The present study demonstrated that KFX, an aqueous extract from P. americana , exhibited potential anticancer effects in a gastric cancer cell line through inhibiting cell proliferation and inducing apoptosis; potentially via the ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel drugs, including Kangfuxin (KFX) oral liquid, Xinmailong injection and cockroach oil have been developed using P. americana as the raw material, with recognized pharmacological activity and clinical efficacy ( 11 – 14 ). A previous study revealed that P. americana extract exhibited significant anticancer effects on the BEL-7402/5-FU Cell line and SGC-7901 cell line ( 15 , 16 ). However, the exact apoptotic effect of KFX remains unclear.…”
Section: Introductionmentioning
confidence: 98%